Social Enterprise Context-Dependent Dynamics In A Global Perspective - Laratta, Rosario (IntechOpen, 2016)
This book is an original, high-quality, research-level work. It sheds lights on the similarities and differences of social enterprise practices across the international scene. Most of the chapters include empirical findings derived from researches conducted by the authors in Middle East and North Africa, East and West Europe, Southeast Asia, and Latin America. From this perspective the book fills an important knowledge gap while also making a contribution to sorting out the competing and contrasting predictions of social enterprise. Through exploring context-dependent dynamics in a global perspective, the authors address potential opportunities and benefits of social enterprise that may help to find solutions to face emerging social needs. Written by leading academics, this book will be of interest not only to students and academics of social enterprise and entrepreneurship but also to those international practitioners who are looking for new approaches for sustainably tackling emerging social challenges.